Development of A Tax Aware Clinic Website for MSMEs - Arniati; Anggraini, Ria; Putri, Wika Arsanti; Kurniawan, Dedi; Maulana Putra, Tengku Surya; Maulana Putra, Anjelina; Hasanah, Afriyanti (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2026)
MSMEs in Indonesia contribute 61.07% to GDP and absorb 97% of the national workforce. However, their income tax contribution was only 1.1% in 2019. This glaring gap indicates that existing tax information channels, including the Directorate General of Taxes (DGT) portal, fail to effectively reach and serve MSMEs. This study aims to analyze the needs of MSMEs for specialized tax services through a dedicated tax clinic web platform. Research data were obtained from 17 informants through in-depth interviews and focus group discussions (FGDs) that were analyzed using open, axial, and selective coding. A key methodological contribution is the direct link between FGD insights and design features: for example, informants' distrust and discomfort with DGT-managed consultations, feeling "interrogated" rather than guided, directly shaped the decision to design the consultation feature as an independent, university-led service, rather than a government portal. These findings suggest that most MSMEs do not rely on official tax websites; Instead, they obtain tax information from WhatsApp, YouTube, and Instagram status updates, indicating low trust and awareness of the current tax portal. Informants require tax regulations categorized by business type, credible and up-to-date news, interactive calculators (PPh Articles 21, 23, and final income tax), visual learning materials, and personalized online consultation services. This study provides a user-centered design framework aligned with the TSEF for a tax clinic website specifically designed for the needs of MSME taxpayers in Batam, offering a replicable model for similar polytechnic institutions across Indonesia seeking to bridge the tax compliance gap.